Molecular and cellular levels organization of life. Genetics : Module 1.Text Book for the students of the first year studying - Prykhodko, A. B.; Popovich, A. P.; Maleeva, A. Y.; Приходько, Олександр Борисович; Попович, Аліса Петрівна; Малєєва, Ганна Юріївна (Zaporozhye state medical university, 2017)
The ‘‘Text-Book” pays attention to the molecular and cellular levels organization of the living organisms and to some problems of Genetics. It deals with topics mentioned in the Academic Curriculum for the Medical University. The questions of each topic act as test-pieces and help to fix the knowledge acquired. The book will contribute to examination success while engendering a genuine love of biology which will stimulate the students to delve further and deeper into the subject.